A new species of carrion-breeding "golden blowfly" from south-eastern Australia (Diptera: Calliphoridae). Issue 2 (3rd July 2021) - Johnston, Nikolas P.; Wallman, James F.
ABSTRACT: The adults and third instar larva of Calliphora pryori sp. nov., a new species of Calliphora Robineau-Desvoidy endemic to south-eastern Australia, are described for the first time. This species breeds in carrion and is very closely allied to C. hilli, with which it is found sympatrically. However, it is less frequently encountered and has only been recorded from southern parts of both South Australia and Victoria. The evolutionary affinities of C. pryori with other members of the C. hilli group are discussed.